PENGARUH MODEL PEMBELAJARAN TARL DALAM MENINGKATAN KEMAMPUAN DASAR LITERASI MEMBACA PESERTA DIDIK KELAS 1 PADA MATA PELAJARAN BAHASA INDONESIA - Kurniawan, Ganang Aji; Dwijayanti, Ida; Susianingsih, Ika (Program Studi Pendidikan Guru Sekolah Dasar Fakultas Pendidikan Ilmu Pengetahuan Sosial dan Bahasa Institut Pendidikan Tapanuli Selatan, 2025)
This study aims to determine the Teaching at The Right Level (TaRL) method has an effect on the basic literacy skills of elementary school students in reading Indonesian language subjects, this study was conducted at SD Negeri Tambakrejo 01 Semarang City. The type of research used is a mixed method using a parallel convergent research design, namely by combining quantitative methods and qualitative methods which then draw conclusions from both. The subjects of this study were students of class IB SD Negeri Tambakrejo 01 Semarang City. The instrument used in the study was a reading questionnaire with 10 values ​​for the quantitative method, while the researcher used observation, interviews, and supporting documents as qualitative instruments. The analysis technique used was the Shapiro-Wilk normality test, and obtained normal data distribution results. Then, the hypothesis test used the Paired Sample T-test and produced a significance value (2-tailed) of the learning outcomes of class IB students at SD Negeri Tambakrejo 01 Semarang City of 0.000 <0.05. So, Ha is accepted. Thus, the conclusion of this study is that there is an influence of the implementation of the Teaching at The Right Level (TaRL) approach on the Indonesian language learning outcomes of class IB students at SD Negeri Tambakrejo 01, Semarang City.